Educational Values in the "Sere Bissu" Performing Arts Ritual in Bone Regency: A Review of Its Meaning and Function - Astuty, Dewi Sri; Ramli, Asia; Sjahrir, Nurlina (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The Sere Bissu ritual performance in Bone Regency is a cultural heritage with significant meanings that have yet to be fully explored, particularly in relation to its role in forming character and community ethics through education. This study examines educational ideals in Bone Regency's Sere Bissu performance through three primary questions: (1) Analyzing performance structure; (2) Identifying educational values; and (3) Analyzing moral educational values' significance and function. This study is descriptive and qualitative. Data collection was carried out through direct observation, in-depth interviews, and documentation during the implementation of the Sere Bissu ritual. This approach was chosen to understand the context and interpretation of values ​​holistically. The research found that (1) Sere Bissu is a ritual performance with multiple stages, including Mappangolo Mappesabbi, Mappakaraja Alusu, Sere Alusu, Sere Mappabbitte, Sere Bibbi, Sere Mangko, Sere Maddampu Alameng, Sere Lemma’, Mammemmang, Maggiri, and Mappatabe. (2) Educational values encompass religious, social, and moral aspects that foster faith, ethics, and cultural character. (3) These educational values emphasize religious devotion, societal harmony, and moral awareness as key foundations in Bugis culture. This study enhances knowledge of educational values by incorporating local wisdom. This study provides practical guidance for educational institutions and cultural activists to conserve and internalize Bugis’ values, particularly in the Sere Bissu rite, as a foundation for national identity.